2014
DOI: 10.2298/gensr1401179m
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genetic variance components for some quantitative traits in rapeseed (Brassica napus L.)

Abstract: Three hybrid combinations obtained by crossing six winter rapeseed cultivars were analyzed for the impact of genes with additive and dominant effects and their interactions with inheritance of plant height and first lateral branch height. The linkage among the expected progeny means was checked using the scaling test method (Mather, 1949), while the estimates of genetic effects and mode of inheritance was made by the Generation Mean Analysis (Mather and Jinks, 1982). The additive dominant mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Previous results about canola indicated that number of pods per plant had the highest direct effect on grain yield in canola. In addition, 1000-grain weight also had a high direct effect on grain yield [23][24][25][26][27][28][29][30]. Tusar-Patra et al [31] concluded that the strongest effect on seed yield was estimated for number of pods per plant followed by number of seeds per pod and 1000 seed weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous results about canola indicated that number of pods per plant had the highest direct effect on grain yield in canola. In addition, 1000-grain weight also had a high direct effect on grain yield [23][24][25][26][27][28][29][30]. Tusar-Patra et al [31] concluded that the strongest effect on seed yield was estimated for number of pods per plant followed by number of seeds per pod and 1000 seed weight.…”
Section: Discussionmentioning
confidence: 99%
“…Khan et al [32] found that number of branches, 1000-seed weight, and pods per plant affected the seed yield per plant. Marjanović-Jeromela et al [26] reported that the strongest direct effect on seed yield per plant was estimated for plant height, followed by that of number of pods per plant. Ghodrati et al [33] found that number of seeds per pod a Promising Industrial Oil Crop 46 was effective on canola seed yield.…”
Section: Discussionmentioning
confidence: 99%
“…Canola, Brassica napus L, belongs to the family Brassicaceae and is cultivated in many parts of the world, standing out as an excellent economic alternative to other human consumable oils and biodiesels (Miri, 2007;Marjanović-Jeromela, 2008). In Egypt, canola has a bright future in contributing to a reduction in oil deficiency gap between production and consumption of edible oils, particularly as it could be successfully grown during winter season on newly reclaimed land outside the old zone of the Nile valley and thus get around competition with other crops grown in the old area of cultivation (Sharaan et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The SDS-PAGE method provides maximum protein based diversity among genotypes; it is cheap and quick method then other molecular methods (ISEMURA et al, 2001;GEPTS and BLISS, 1988;IQBAL et al, 2005;JAVID et al, 2004;RAHMAN and HIRATA, 2004). Various biochemical and molecular methods are used to study genetic diversity among different crop species/sub-species (VERMA et al, 2015;GOODARZI et al, 2015;IZADPANAH et al, 2015;MARJANOVIC-JEROMELA et al, 2014;HENAREH et al, 2016).…”
Section: Genetic Similarity Matrix and Cluster Analysis Study Of B Rmentioning
confidence: 99%